Feasibility of Serial Ultrasound Measurements of the Rectus Femoris Muscle Area to Assess Muscle Loss in Patients Awaiting Liver Transplantation in the Intensive Care Unit. Issue 11 (November 2020) - Pita, Alejandro; Ziogas, Ioannis A.; Ye, Fei; Chen, Yufan; Rauf, Muhammad A.; Matsuoka, Lea K.; Kaur, Navpreet; Whang, Gilbert; Zielsdorf, Shannon M.; Bastas, Gerasimos; Izzy, Manhal; Alexopoulos, Sophoclis P.
Abstract : Background: End-stage liver disease (ESLD) patients requiring intensive care unit (ICU) care before liver transplantation (LT) often experience significant muscle mass loss, which has been associated with mortality. In this exploratory study, we primarily aimed to assess the feasibility of serial ultrasound (US) rectus femoris muscle area (RFMA) measurements for the evaluation of progressive muscle loss in ICU-bound potential LT candidates and describe the rate of muscle loss as assessed by sequential US RFMA measurements. Secondarily, we sought to identify patient characteristics associated with muscle loss and determine how muscle loss is associated with survival. Methods: We prospectively enrolled 50 ESLD adults (≥18 y old) undergoing evaluation for LT candidacy in the ICU. A baseline computed tomography measurement of psoas muscle area (PMA) and serial bedside US measurements of RFMA were obtained. The associations between patient characteristics, PMA, RFMA, ICU stay, and survival were analyzed. Results: Rapid decline in muscle mass by RFMA measurements was ubiquitously present and correlated to baseline PMA and length of ICU stay. RFMA normalized by body surface area decreased by 0.013 cm 2 /m 2 (95% confidence interval, 0.010-0.016; P < 0.001) for each day in the ICU. Decreased RFMA normalized by body surface area was associated with poor overall survival (adjusted hazard ratio, 0.42; 95% confidence interval, 0.18-0.99; P = 0.047). Conclusions: In this exploratory, prospective study, serial US RFMA measurements in ESLD patients in the ICU are feasible, demonstrate progressive time-dependent muscle loss, and are associated with mortality. Further large-scale assessment of this modality compared with static PMA or performance-based dynamic assessments should be performed.